If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1080 + -1x = 163 Solving 1080 + -1x = 163 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1080' to each side of the equation. 1080 + -1080 + -1x = 163 + -1080 Combine like terms: 1080 + -1080 = 0 0 + -1x = 163 + -1080 -1x = 163 + -1080 Combine like terms: 163 + -1080 = -917 -1x = -917 Divide each side by '-1'. x = 917 Simplifying x = 917
| -24=-12w | | -7=3v+2 | | 24=-w/6 | | 4z/7-5=-2 | | 144+12c=300 | | 2*2*2+-3*-3= | | 1080*x=955 | | -u/6=-42 | | 20=2+3u | | (7x^4)/(sqrt(2x-8)) | | 2.3log(x)=3log(6-x) | | 6x+y+z=10 | | -4u+5=5-4u | | 1920*x=5 | | -15=4u-3 | | 4lnx-1=6 | | 5/4=7x^2-x | | 42+x=(13+x)*2 | | 21y+7=5 | | 5/2*32 | | Y=-xy-3x-3 | | 11=2/3x-3 | | 2y=5y-8 | | 1920*x=2 | | x-(0.75x+1)=1 | | 4=4xW | | 4x^3+18x=0 | | 7-3-2/5v | | 3x-(x+1)=9 | | x+55=4x-5 | | 0=60+12.5x-4.9x^2 | | -16+3=-24+8x |